Potential of RFID telemetry for monitoring ground-dwelling beetle movements: A Mediterranean dry grassland study - Blight, Olivier; Geslin, Benoît; Mottet, Lola; Albert, Cécile H. (Frontiers in Ecology and Evolution, 2023)
Better understanding insects’ movements could help preserve and restore the insect communities that are key to the functioning of grasslands. Recent technological advances have led to spectacular achievements in movement ecology, making it possible to track the individual movements of a wide variety of organisms, including the smallest. However, monitoring systems such as RFID tags may negatively impact an organism’s life history, with potential consequences on the reliability of data and conclusions. This study explored the potential of passive RFID tags to track the movements of three small ground-dwelling beetle species, a predator (Poecilus sericeus, Carabidae), a detritivore (Asida sericea, Tenebrionidae) and a granivore (Acinopus picipes, Carabidae), in a Mediterranean dry grassland degraded by years of cultivation. First, we tested whether carrying tags might impact individuals’ behaviour, using a before-and-after design under laboratory conditions. Despite a trend toward shorter displacements, we found no significant short-term effect of the tags on individuals’ movements. Second, we tracked a total of 25 tagged beetles in their natural environment every 4 h for 48 h. We highlight the principal limitation of using passive tags with small terrestrial beetles: the antenna has to pass over the tags to detect them, which restricts tracking to a few consecutive days after which the probability of locating an individual is low. However, the data obtained sheds light on the biological rhythms and daily movement capabilities of our target species: A. sericea is more mobile and P. sericeus less mobile than expected. Such knowledge could help predict the species’ ability to recolonise degraded areas, enabling appropriate restoration actions to be designed based on landscape ecology principles.